Efficient direct rendering of deforming surfaces via shared subdivision trees. (January 2015) - Liu, Fuchang; Martin, Tobias; Yeung, Sai-Kit; Gross, Markus
Abstract: In this paper, we present a subdivision-based approach to rasterize implicit surfaces embedded in volumetric Bézier patches undergoing a nonlinear deformation. Subdividing a given patch into simpler patches to perform the surface rasterization task is numerically robust, and allows guaranteeing visual accuracy even in the presence of geometric degeneracies. However, due to its memory requirements and slow convergence rates, subdivision is challenging to be used in an interactive environment. Unlike previous methods employing subdivision, our approach is based on the idea where for a given patch only one subdivision tree is maintained and shared among pixels. Furthermore, as the geometry of the object changes from frame to frame, a flexible data structure is proposed to manage the geometrically varying Bézier patches. The resulting algorithm is general and maps well to parallel computing platforms such as CUDA. We demonstrate on a variety of representative graphics and visualization examples that our GPU scheme scales well and achieves up to real-time performance on consumer-level graphics cards by guaranteeing visual accuracy. Highlights: We present Shared Subdivision Trees (SST) to rasterize implicit surfaces on GPUs. We address the problem of efficiently rendering implicit surfaces which undergo a nonlinear deformation throughout the rendering process. We map Shared Subdivision Trees well to parallel computing platforms such as CUDA.